Development and Validation of the CHD-PEBBS: A Scale to Assess Perceived Exercise Benefits and Barriers in Coronary Heart Disease Patients - Liu Y; Feng L; Wang L; Li H; Tu H; Li X; Zhang X; Zhang L; Yang M; Sun X; Huang T; Xiong Y (Patient Preference and Adherence)
Yu Liu,1,* Linmei Feng,2,* Luyao Wang,1,* Hongyan Li,1,3 Hui Tu,4 Xin Li,5 Xiaotian Zhang,1 Lingzhu Zhang,1 Minhui Yang,1 Xin Sun,1 Tingting Huang,1 Yuxin Xiong1 1School of Nursing, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 2Department of Operating Theatre, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 3Jiangxi Province Key Laboratory of Aging and Disease, Nanchang University, Nanchang, Jiangxi Province, People’s Republic of China; 4Department of Nursing, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 5Department of Cardiology, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongyan Li, School of Nursing, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Email Janet_lhy@163.comBackground: The level of perceived exercise benefits and barriers is one of the key influencing factors of cardiac exercise rehabilitation (CER). There is a lack of validated tools to assess coronary heart disease (CHD) patients’ exercise perception.Purpose: The aim of this study is to develop a scale assessing CHD patients’ perceived exercise benefits and barriers (CHD-PEBBS) and test its reliability and validity.Methods: A total of 205 CHD patients were recruited for a cross-sectional survey. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to extract factors, delete items and evaluate construct validity. The Cronbach’s alpha coefficient and test–retest reliability were used to test the reliability of the scale.Results: Based on the health belief model, this study developed a perceived benefits and barriers framework. CFA showed that the fit indices (such as χ2/df=2.281, CFI=0.93, RMSEA=0.079) were all acceptable A total of 6 factors were extracted through EFA, with a cumulative variance contribution rate of 75.52%. The perceived benefits subscale included 3 dimensions: “improving physiological indicators”, “improving quality of life” and “improving physiological function” with a total of 12 items. The perceived barriers subscale also included 3 dimensions: “lacking of exercise support”, “worrying about adverse consequences” and “poor exercise experience or perception” with a total of 10 items. The Cronbach’s alpha coefficient of the scale was 0.917, and the test–retest reliability was 0.941.Conclusion: The CHD-PEBBS shows good reliability and validity, which may be used to evaluate the CER perception level of CHD patients, offering precise targets and pathways for exercise rehabilitation interventions in nursing.Keywords: barriers, benefits, coronary heart disease, cardiac rehabilitation exercise, scale development